Creating inequality by spoiling their sons? : Women's views of mothers bringing up children in Tornedalen (Northernmost Sweden) - Juntti-Henriksson, Ann-Kristin (Luleå tekniska universitet, Medier ljudteknik och upplevelseproduktion och teater, 2008)
Godkänd; 2008; 20101129 (akijuh)